1999
DOI: 10.1046/j.1537-2995.1999.39111247.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of ABO chimeras and mosaicsusing hematopoietic colony‐derived DNA

Abstract: The subjects without MDS had two distinct hematopoietic cell lineages that led to their ABO chimeric status. The subject with MDS was assumed to have an ABO mosaicism caused by the somatic deletion of the ABO gene in the hematopoietic progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Indeed, over 500 million different blood tests were carried out over 50 years for different purposes (maternity, blood donations or surgery) and fewer than 500 chimera have been discovered [9,10,13,14,16,17]. Because a chimera is a very rare event [47], it is not the duty of anti-doping laboratories to conduct DNA analyses to demonstrate that a positively tested athlete is in reality a natural chimera.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, over 500 million different blood tests were carried out over 50 years for different purposes (maternity, blood donations or surgery) and fewer than 500 chimera have been discovered [9,10,13,14,16,17]. Because a chimera is a very rare event [47], it is not the duty of anti-doping laboratories to conduct DNA analyses to demonstrate that a positively tested athlete is in reality a natural chimera.…”
Section: Discussionmentioning
confidence: 99%
“…We also applied molecular methods to study the blood group and the DNA polymorphisms of peripheral blood and marrow (see Table 1). The sixth and seventh exons of the ABO gene were amplified and sequenced with specific primers 2 . The result of sequence‐based typing of the blood group was ABO * 0101 , 0201 , and it was confirmed that granulopoiesis came from the donor.…”
Section: Rbc Typings and Dna Polymorphisms Demonstrating Mixed Chimmentioning
confidence: 93%
“…Use nonagglutinating (IgG) antibodies Chemically convert agglutinating IgM pentamers into nonagglutinating IgM monomers, e.g., using dithiothreitol [48,57] or 2-mercaptoethanol Purify IgG fractions of sera on Protein G [49] Dilute antisera past point of agglutination Avoid use of potentiators Chemically fix the RBCs prior to incubation with anti-A, -B, -M, or -N, e.g., with dimethylsuberimidate [74], formaldehyde [47,75], or glutaraldehyde [13,21,44,49] To avoid agglutination caused by secondary antibody:…”
Section: Selection Of Direct or Indirect Labeling Methods For Each Blomentioning
confidence: 99%
“…The analysis of mixed RBC populations occurring as a result of hematopoietic chimerism in twins [42][43][44][45][46] and in bone marrow transplant recipients [47][48][49][50][51][52] is easily performed by flow cytometry. This technique has also been used in studies of individuals with blood group mosaicism [26,[53][54][55].…”
Section: Chimerism and Mosaicismmentioning
confidence: 99%
See 1 more Smart Citation